2012
DOI: 10.1136/jnnp-2011-300980
|View full text |Cite
|
Sign up to set email alerts
|

Visual hallucinations in the differential diagnosis of parkinsonism: Table 1

Abstract: Visual hallucinations (VH) occur commonly in Parkinson's disease (PD) and dementia with Lewy bodies (DLB) but are reported much less frequently in other neurodegenerative causes of parkinsonism, such as progressive supranuclear palsy, multiple system atrophy and corticobasal degeneration syndrome. This clinical sign may be helpful when considering the differential diagnosis of patients with parkinsonism. The observation that VH may be specific to Lewy body pathology probably reflects a greater vulnerability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 68 publications
3
32
1
Order By: Relevance
“…These types of vivid and realistic hallucinations were previously reported in MSA patients (14) and they bear clinical resemblance to pedunculer hallucinosis. Peduncular hallucinosis may occur as a result of damage to the brainstem reticular formation or thalamus' input pathways, or the inhibitory serotoninergic neurons associated with raphe nucleus (15). Cerebellar vermis' connection to reticular formation, raphe nucleus and thalamus (16,17) satisfy the necessary anatomical basis for this condition and strengthen the possibility that the hallucinations seen in our case were peduncular hallucinations when the clinical findings are taken into account.…”
Section: Discussionsupporting
confidence: 69%
“…These types of vivid and realistic hallucinations were previously reported in MSA patients (14) and they bear clinical resemblance to pedunculer hallucinosis. Peduncular hallucinosis may occur as a result of damage to the brainstem reticular formation or thalamus' input pathways, or the inhibitory serotoninergic neurons associated with raphe nucleus (15). Cerebellar vermis' connection to reticular formation, raphe nucleus and thalamus (16,17) satisfy the necessary anatomical basis for this condition and strengthen the possibility that the hallucinations seen in our case were peduncular hallucinations when the clinical findings are taken into account.…”
Section: Discussionsupporting
confidence: 69%
“…34 In contrast, synucleinopathies without Lewy bodies, such as multisystem atrophy, have a low incidence of visual hallucinations. 35 Lewy Body Dementia. Lewy body dementia is the second most common form of dementia after Alzheimer disease.…”
Section: 32mentioning
confidence: 99%
“…Visual hallucinations form part of the core clinical diagnostic criteria for Lewy body dementia and are typically seen early in the course of the disease, before the development of Parkinsonian motor symptoms. 36 The incidence of VHs in Lewy body dementia varies between 20% and 75%, 31,33,35 and the presence of VH provides an 83% positive predictive value for distinguishing Lewy body dementia from Alzheimer disease. 37 VHs in Lewy body dementia typically manifest as prolonged well-formed complex scenes of figures and objects and provoke varied reactions from fear through to indifference.…”
Section: 32mentioning
confidence: 99%
“…Various brainstem structures are known to be involved in regulation of sleep (Boeve et al, 2007), and disruption to serotonergic and cholinergic outputs from the brainstem to the thalamus may play a role in the development of visual hallucinations (Bertram and Williams, 2012). Sleep studies in PD camptocormia show an increased rate of periodic leg movements of sleep (Lavault et al, 2009) and one study suggested reduced midbrain and pontine size may explain this correlation (Bonneville et al, 2008).…”
Section: Pathophysiologymentioning
confidence: 99%